Pemikiran Tafsir Sunda (Analisis Ayat Suci lenyepaneun) - Jujun Juanda; Satria Khresna W (LP2M Universitas PTIQ Jakarta, 2017)
This article discusses the interpretation of the exegesis book of Lelenyapaneun, emphasizing regional characteristics, responding to the situation in the society and the traditional picture and the unique nature of Sunda. So the pattern of interpretation became a social literature (adabi Ijtimai), method tahlily (analysis) that combine the traditional method and the use of reason (ra'yu). As a subtitle of regional interpretation, Mohammad E. Hasim has succeeded in displaying regional sides that are in line with the needs of the people, answers to current issues and preparations for the future. Despite the localities, this interpretation can only be read by people who understand Sundanese, but from the perspective of writing, insight and contextuality of the local, this interpretation has succeeded in describing the progress of scientific treasures in pasundan.